More than kin, less than kind: one family and the many faces of diabetes in youth - Luciana F. Franco; Renata Peixoto-Barbosa; Renata P. Dotto; José Gilberto H. Vieira; Magnus R. Dias-da-Silva; Luiz Carlos F. Reis; Fernando M. A. Giuffrida; Andre F. Reis (Archives of Endocrinology and Metabolism)
SUMMARY Identification of the correct etiology of diabetes brings important implications for clinical management. In this report, we describe a case of a 4-year old asymptomatic girl with diabetes since age 2, along with several individuals in her family with different etiologies for hyperglycemia identified in youth. Genetic analyses were made by Sanger sequencing, laboratory measurements included HbA1c, lipid profile, fasting C-peptide, pancreatic auto-antibodies (glutamic acid decarboxylase [GAD], Islet Antigen 2 [IA-2], and anti-insulin). We found a Gly178Ala substitution in exon 5 of GCK gene in three individuals co-segregating with diabetes, and type 1 diabetes was identified in two other individuals based on clinical and laboratory data. One individual with previous gestational diabetes and other with prediabetes were also described. We discuss difficulties in defining etiology of hyperglycemia in youth in clinical practice, especially monogenic forms of diabetes, in spite of the availability of several genetic, laboratory, and clinical tools.